Development of colorimetric lateral flow assay for quantitative detection of anti-doping markers in sports - Sharma, Antareep (Nanyang Technological University, 2020)
Doping in sports is defined as the use of substances, both foreign and physiological, in an unnatural manner or in abnormal quantities to enhance an athlete’s performance in competitions. The current doping control mechanisms involve randomized testing of samples from athletes using laboratory techniques, which are typically cumbersome with extremely long turnaround times and are not cost effective. This reduces the efficiency of the screening process as a large number of athletes are not tested for doping. Point of care tests (POCTs) such as lateral flow assays (LFAs) can be a viable solution to increase the testing frequency and make this screening more effective by allowing large scale testing with a much smaller cost compared to laboratory tests. LFAs have several advantages over laboratory tests; they are versatile, highly mobile, require minimal sample volume, can correlate to laboratory tests without expensive instrumentation and have a rapid turnaround time, making them perfectly suited to be utilized for on-site screening tests. However, LFAs face challenges such as sensitivity, especially for visual analysis of results, which inhibits their widespread commercial usage. Thus, there is a need to develop strategies to address these challenges and improve LFA performance, especially for reliable on-site testing without involving complicated instrumentation or sophisticated testing protocols. This thesis aims at exploring strategies to improve LFA sensitivity for analysis of complex matrices. In the first study, a novel LFA layout was developed to reduce the interference from matrix components on LFA responses. By incorporation of a magnetic bead (MB) based sample preconcentration step in the LFA, a sensitive colorimetric assay, with a visual limit of detection (LOD) of 10 ng/ml in plasma was demonstrated within a 15 min assay time. In order to improve the sensitivity, a novel nucleation-based signal amplification technique utilizing a composite signal reporter was developed in the second study. A colorimetric gold nanoparticle conjugated magnetic bead (GMB) reporter was synthesized to be used as a precursor for nucleation of gold on its surface, which enabled formation of large clusters at the test line, improving the visual sensitivity of the assay. This strategy resulted in a highly sensitive assay with a visual LOD of 0.1 ng/ml in plasma within a total assay time of 20 min. In both of these studies, a Troponin model system, involving Troponin ICT analyte and anti-Troponin I and anti-Troponin C antibodies, was utilized to validate the results. Troponin is an important marker for skeletal and cardiac muscle regulation and is a well-studied system for LFA studies. The LFA strategies developed were then translated to detect Insulin like Growth Factor-1 (IGF-1) using anti-IGF-1 antibodies. IGF-1 is a prohibited substance in competitive sports and also a biomarker for Growth Hormone (GH) doping. IGF-1 assay, incorporating MB based sample pretreatment into the LFA, resulted in a visual LOD of 1 μg/ml in plasma, whereas the assay involving signal amplification via GMB reporters resulted in a promising visual LOD of 100 ng/ml in plasma, which was well below the allowable limit for IGF-1 in competitive sports. The third and final study is on improving the robustness of the LFA by replacing traditional antibodies with affimers, which have similar affinities towards the analytes, but a much better stability as compared to antibodies. Using an Interlukin-8 (IL-8) model system, consisting of anti-IL-8 affimer conjugated magnetic beads for colorimetric detection, a visual LOD of 1 ng/ml was obtained in PBS, which is near the physiological range of IL-8 in injured athletes. This thesis serves as a template for future studies in LFA technologies in three main directions: development of alternative LFA layouts, innovative use of reporters and utilization of novel recognition molecules. The strategies adopted in this thesis resulted in highly sensitive assays, with LODs well within the clinically relevant ranges of the analytes in human plasma. The validation of these assays in a complex matrix such as plasma provides opportunities for on-site application of LFAs. Moreover, the generic approach of these proposed strategies allows for translation of these LFAs to detect several other biomolecules.